European Green Deal: Slowing Down Multi-Speed Integration with Innovation - Axarli, Dimitra (HAPSc Policy Briefs Series, 2021)
With the creation of the Green Deal, the European Union aims to achieve the goal of climate-neutrality by 2050. Multi-speed European integration is very likely to take place during the procedure of transition, if the proper precautions are not taken. Although this would not necessarily be a reason to be concerned about in other cases, in the case of climate-neutrality would be most distressful. That is because of the lack of justness multi-speed transition carries and the nature of the goal itself. Although the EU has created a whole mechanism to reassure that the transition will take place in a fair and just way, it concentrates on regions with specific features (such as fossil and carbon dependency), leaving behind other, less concerning regions. This Policy Brief aims to create a link between the Just Transition Mechanism and the possibility of multi-speed integration and to propose an additional pillar that –even though might seem gentler- may be enough to prevent this issue. That is, the creation of several model-like projects from the European Commission, that could be proposed and applied in almost any region. One of these projects could be the innovative Vertical Agriculture scheme.